Pengaruh Ice Breaking Terhadap Motivasi Belajar Matematika Kelas VIII di Madrasatul Wustha Pondok Pesantren Raudhatul Ulum Kabupaten Solok - Jaya, Salmi Indra; Zaimil, Roza; Adel, Adevi Murni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research is motivated by the low learning motivation of the students, which is indicated by a lack of concentration during lessons, not paying attention to the teachers when explaining, entering and leaving the classroom, and even some falling asleep during the learning process. Based on this condition, the researcher conducted a study to determine the effect of ice breaking on the learning motivation of eighth-grade students at Madrasatul Wustha Pondok Pesantren Raudhatul Ulum in Solok Regency. This research is a quantitative study with a population of all eighth-grade students totaling 16 individuals. The sampling technique used was total sampling. Data was collected through questionnaires and analyzed using simple linear regression with the help of SPSS software. The results of the hypothesis test showed that the t-count value = 1.573 and the t-table value = 1.761. Based on the testing criteria, since t-count < t-table, H0 is rejected and H1 is accepted. Therefore, it can be concluded that there is a significant effect of ice breaking on the learning motivation of eighth-grade students at Madrasatul Wustha Islamic Boarding School Raudhatul Ulum in Solok Regency